(untitled) (Socio-economic relations in the digital society, 2019)
The article examines a minimum wage, as institute of adjusting of profi ts of population. For research two groups of methods are used: historical method of research and methods of statistical analysis, including cross-correlation analysis. In the article the analysis of salary is conducted in the structure of resources and profi ts of households for 1999–2015 biennium. Becoming of minimum wage is investigational as an institute of adjusting of wage and incomes. Three hypotheses are in-process suggested in relation to interdependence of middle salary and GDP on one busy, middle salary and middle profi ts of households, middle and minimum salary, and their verifi cation is conducted on the basis of statistical data and previous researches of authors. Th e studies established a close relationship between the real average monthly indexes of GDP on one busy, the wages, minimum wages and household income per person. Confirming the fact of implementation of the minimum wage as an institution-control wage formation and household income.